2001
DOI: 10.1200/jco.2001.19.2.425
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Adjuvant to Radical Nephrectomy in Robson Stages II and III Renal Cell Carcinoma: A Multicentric Randomized Study

Abstract: Adjuvant rIFNalpha2b is not indicated after radical nephrectomy for renal cell carcinoma. The protective effect in the small group of pN2/pN3 patients requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
104
1
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(116 citation statements)
references
References 13 publications
5
104
1
6
Order By: Relevance
“…It is unlikely that adjuvant or salvage therapies have contributed to a significantly longer survival, because most historic regimens are associated with a dismal effect on survival. [15][16][17][18] Despite these limitations, our findings are novel and offer a new perspective about the effect of age on RCC prognosis. In addition, the sample size makes our findings highly generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that adjuvant or salvage therapies have contributed to a significantly longer survival, because most historic regimens are associated with a dismal effect on survival. [15][16][17][18] Despite these limitations, our findings are novel and offer a new perspective about the effect of age on RCC prognosis. In addition, the sample size makes our findings highly generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…The adjuvant use of IFN following metastasectomy has not been tested, but its use on an adjuvant schedule in high-risk patients who did not have metastatic cancer has been reported and appears not useful. 52 A trial of the addition of 13-cis-retinoic acid to an outpatient schedule of IFN-α was reported by Motzer et al 53 The combination arm had a 12% vs 6% (P=.14) overall response rate, 19% of patients in the combination arm were progression-free at 24 months compared with 10% in the second arm, and longer duration of responses were achieved (33 vs 22 months, P=.03). However, median survival was comparable (P=.26), and quality of life was poorer for the combination arm, especially during the first 8 weeks of treatment.…”
Section: Phase III Outcomesmentioning
confidence: 99%
“…However, recent studies employing a-IFN-based therapy in the adjuvant setting for renal cell carcinoma patients also did not result in significant improvement regarding relapse-free survival and overall survival (Pizzocaro et al, 2001;Messing et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In studies of Pizzocaro et al (2001), an adjuvant treatment with IFN-alfa2b demonstrated a decrease in relapse rates in 26 patients with extensive nodal disease (pN2/pN3), but an increase in recurrence rates in node negative renal carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%